EPISTEMOLOGI IDEALISTIK SYEKH AZ-ZARNUJI TELAAH NASKAH TA’LIM AL MUTA’ALIM - Hilman Haroen (Profetika: Jurnal Studi Islam, 2014)
Az-Zarnuji proposes four considerations of strengthening the right intentionin looking for science. First, looking for a science is regarded as the religion task; second, looking for a science must be intended as an effort of getting happiness of life in the future; third, in looking for a science, it is properly awaken again to the Islamic teaching and religion; fourth, looking for a science is supposed to the frame of conveying the thanksgiving to Allah. The characteristic of Az-Zarnuji epistemology says that looking for a science is the religion task. It shows that Az-Zarnuji epistemology becomes Islamic epistemology, standard and traditional with idealistic type. It is a idealism containing many things, integration between organic and thinkingcomprehensively (reality, form) or absolutism consisting of the meaning as 1) view of life, the truth must be valuable, reality, final and forever objective. 2) There is only one belief and one explanation objectively, no change and right to the reality. The religion epistemology of Az-Zarnuji stresses on the characteristics of God, society and individuality with epistemology of principality based on utility principle. The implementation of science system is for thecase of the three characteristics above. The stress goes to the quality or religion ethicvalues. The concept of Az-Zarnuji epistemology is ideological focusing on value and the Islamic religion (theology) or faith epistemology.Key Words: epistemology; Islamic education;science; religion ethic.Az-Zarnuji menawarkan empat pertimbangan yang memperteguh niat yangbenar dalam mencari ilmu pengetahuan. Pertama, menuntut ilmu dianggap sebagaitugas agama; kedua, menuntut ilmu seharusnya dimaksudkan usaha memperolehkebahagiaan hidup di kemudian hari; ketiga, dalam menututi lmu, seyogyanyamembangkitkan kembali agama dan syiar Islam; Keempat, menuntut ilmu ditujukandalam rangka menyampaikan puji syukur kepada Tuhan. Ciri khas epistemologi Az-Zarnuji, epistemologi agama, menuntut ilmu tugas agama, ini menjadikan epistemologiAz-Zarnuji merupakan epistemologi Islam, baku dan kuna (Tradisional) bertipe idealistik.Idealistik adalah pandangan ideal (idealism) atau mencakup segala sesuatu, kepaduanpikiran dan organik saling terkait bersifat sempurna (realitas, wujud) atau Absolutisme,mencakup makna sebagai 1).Pandangan bahwa kebenaran (nilai, realitas) nyata, finaldan abadi secara obyektif. 2) Keyakinan hanya ada satu penjelasan obyektif tak berubahdan benar tentang realitas. Epistemologi religious (agama) Az-Zarnuji menekankanpada ciri Ketuhanan, individualitasdan masyarakat, dengan azas epistemologi yangmendasarinya azas manfaat (utility). Pelaksanaan sistem ilmu pengetahuan dalamrangka ketiga ciri tersebut. Penekanan pada kualitas atau pada nilai etika religious.Konsep epistemologi Az-Zarnuji bersifat ideologis, bertumpu pada nilai dan ajaran(teologi) Islam atau epistemologi iman (ketauhidan).Kata Kunci: epistemology; pendidikan Islam; ilmu Pengetahuan; etika Religius.